เครื่องสไลด์กล้วยตามแนวยาวและขวาง Longitudinal and Horizontal-aligned Banana Slicing Machine - ศิริพรอัครชัย สิทธิบูรณ์; ศิริพรอัครชัย ธัญทิพย์ (RMUTP Research Journal Sciences and Technology, 2016)
บทคัดย่อ การวิจัยนี้จัดทำขึ้นเพื่อปรับปรุงเครื่องสไลด์กล้วยรุ่นเก่าซึ่งสไลด์ได้ในแนวยาวเพียงอย่างเดียว โดยการออกแบบ สร้าง และทดสอบ เครื่องสไลด์กล้วยรุ่นใหม่ ให้สามารถสไลด์กล้วยดิบให้เป็นแผ่นตามแนวยาวและตามแนวขวางได้ทั้งแบบแผ่นเรียบและแผ่นหยัก ปรับความหนาการสไลด์ได้ระหว่าง 1-2 มิลลิเมตร โดยเครื่องจักรรุ่นใหม่จะประกอบไปด้วย แผ่นน้ำหนักกดที่ติดตั้งอยู่เหนือซองบรรจุกล้วย และซองบรรจุกล้วยสามารถบรรจุกล้วยได้ครั้งละไม่น้อยกว่า 5 ผลในแนวนอน และ 10 ผลในแนวตั้ง มีใบมีดที่ติดตั้งบนจานสไลด์ และมีถาดลำเลียงออกสอดอยู่ใต้จานสไลด์เพื่อรองรับผลผลิต ใช้มอเตอร์เกียร์เป็นต้นกำลังสำหรับขับหมุนจานสไลด์ ตัวเครื่องจักรมีความกว้าง 0.56 เมตร ยาว 0.64 เมตร และสูง 1.38 เมตร การทดสอบทำการสไลด์ที่ความหนา 1.5 มิลลิเมตร ทั้งแบบแผ่นเรียบและแผ่นหยัก จะได้อัตราการสไลด์เฉลี่ย 167 กิโลกรัม/ชั่วโมง มีเกณฑ์ความคลาดเคลื่อนเฉลี่ย ± 0.02 มิลลิเมตร และมีเปอร์เซ็นต์ความหนาผิดพลาดเฉลี่ย ±1.05 เครื่องจักรมีอัตราการสิ้นเปลืองพลังงานไฟฟ้าเฉลี่ย 0.23 กิโลวัตต์-ชั่วโมง ภายใต้การนำเครื่องจักรไปใช้โดยกลุ่มชุมชนเป้าหมายที่มีต้นทุนการผลิต 4.78 ล้านบาท/ปี จะมีกำไรสุทธิประมาณ 5.97 ล้านบาท/ปี และมีระยะเวลาการคืนทุนประมาณ 0.82 ปี คำสำคัญ : เครื่องสไลด์ กล้วย กล้วยฉาบ Abstract This research was developed from the old version of the banana slicing machine for slices a banana in sheet-form longitudinal axis only by designed, constructed and tested a new version of the banana slicing machine for slices a banana in sheet-form longitudinal and horizontal axis in flat-shape and curly-shape and adjustable sheet-thickness at between 1-2 mm. The new version of the machine would consist of a pressure plate over the feeding channel. The feeding channel could support for 5 fruits of a banana in the longitudinal laying and support for 10 fruits in the horizontal laying. The blade was installed on a drum and the tray was inserted under the drum for finished products. Electric gear-motor was used to drive the drum. The overall dimensions of the machine ware 0.56m (width)0.64m (Length)1.38m (High). The experimental was sliced by the machine at 1.5 mm thick in flat-shape and curly-shape can be summarized; the average rate of slide was 167 kg/hr. The average tolerances of sliced was ±0.02 mm, the average deviations percentage of sliced was ±1.05 and the average power consumption of the machine was 0.23 kWh. The machines were used by targeted communities, with production costs of about 4.78 million baht/year will lead a net profit to 5.97 million baht/year and the payback period of about 0.82 years. Keywords : Slicing Machine; Banana; Banana Chips